Blog and freedom of speech in Malaysia / Raja Mohd Iskandar Zulkharnian Raja Abdul Malek … [et al.] - Raja Abdul Malek, Raja Mohd Iskandar Zulkharnian; Abdullah, Nur Aleeya Aria Nyakot; Khushaini, Nor Aliza; Abdul Ghani, Azrimawati (Faculty of Law, 2012)
Although there has been studies or researches done related to this topic or issue but those research does not cover the relevance and applicability of Section 3, 233, 211 of Communication and Multimedia Act 1998 [Act 588] to control the bloggers in express their comment online the legal reason why this act should come into force. This purpose of this research is to analyst as to the interpretation of the freedom of speech under Article 10(l)(a), the restrictions under Article 10 (2) of Federal Constitution and the inconsistency of Section 3, 233, 211 of Communication and Multimedia Act 1998 [Act 588] with Federal Constitution Under Article 10 Federal Constitution, every citizen has the right to express themselves by way of verbal or written on any issues arise. This study will also will look whether or not Section 3, 233, 211 of Communication and Multimedia Act 1998 [Act 588] violating blogger's freedom o'f speech in our country because Section 233 of CMA have prevented any person who using network facilities and network service having knowledge to creates solicits and initiates any obscene comment, indecent, false, menacing or offensive in character with intention to annoy, abuse, threaten or harass another person commits an offence and Section 211 of CMA imposed to the blogger to control their blog and failure to comply with these two sections will result to an offences and punishable under Section 233(3) of CMA to a fine not exceeding RM50,000 and 2 years imprisonment or both. We will also make a comparison between freedom of speech and its application on the internet in Malaysia as well as in United States. Moreover, there have been many cases where the accused had been charge in the court of law and their blogs had been blocked even before the court rule judgment. These researches also will do analyst the use and limitation of the exclusion clause or disclaimer as a defense in blogs on the internet for future benefit.